2016
DOI: 10.3847/0004-6256/151/4/90
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Through the Ring: Near-Infrared Photometry of V582 Mon (Kh 15d)

Abstract: We examine the light and color evolution of the T Tauri binary KH 15D through photometry obtained at wavelengths between 0.55 and 8.0 µm. The data were collected with ANDICAM on the 1.3 m SMARTS telescope at Cerro-Tololo Inter-American Observatory and with IRAC on the Spitzer Space Telescope. We show that the system's circumbinary ring, which acts as a screen that covers and uncovers different portions of the binary orbit as the ring precesses, has reached an orientation where the brighter component (star B) f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
(60 reference statements)
2
13
0
Order By: Relevance
“…Wider binaries can experience periodic dimming as components of the binary pass behind a circumbinary disk, as is the case in KH 15D (e.g., Windemuth & Herbst 2014;Arulanantham et al 2016). The 131-day-period WL 4 system and the 93-day-period YLW 16A system (Plavchan et al 2013) show similar dimming behavior, suggesting a similar origin for their variability.…”
Section: Discussionmentioning
confidence: 79%
“…Wider binaries can experience periodic dimming as components of the binary pass behind a circumbinary disk, as is the case in KH 15D (e.g., Windemuth & Herbst 2014;Arulanantham et al 2016). The 131-day-period WL 4 system and the 93-day-period YLW 16A system (Plavchan et al 2013) show similar dimming behavior, suggesting a similar origin for their variability.…”
Section: Discussionmentioning
confidence: 79%
“…However, the circumbinary disk eluded detection. The system shows no infrared excess emission out to 8 µm (Arulanantham et al 2016), in line with the relatively large inner dust edge. In addition, the dust ring has not been detected at millimeter wavelengths with SMA or ALMA.…”
Section: Introductionmentioning
confidence: 73%
“…Chiang & Murray-Clay (2004) argued that the disk of KH 15D cannot extend beyond ∼5 au to maintain rigid precession and explain the long-term photometric variability of the system (but see Lodato & Facchini 2013 for the possibility of the disk extending to 5-10 au). Recently, Arulanantham et al (2016) confirmed the rigid precession of the ring and estimated a velocity (across the sky) of ∼15 m s −1 for the projected edge of the ring. Then, the precession rate of the ascending node of the ring can be estimated to be 0.…”
Section: Inner and Outer Truncation Of The Diskmentioning
confidence: 88%
“…During the time between 2010 and 2012, both stars A and B were only detectable through scattered light. Currently, the brightness of the system has increased as star B's orbit has become uncovered from the the trailing edge of the precessing disc (Capelo et al 2012;Windemuth & Herbst 2014;Arulanantham et al 2016;Aronow et al 2018).…”
Section: Circumbinary Disc Of Kh 15dmentioning
confidence: 99%
“…The obscuring material likely consists of solids that form a dust embedded layer within the gaseous disc. IR observations suggest that the solids consists of 1 to 50 micron size particles (Arulanantham et al 2016(Arulanantham et al , 2017. We define the full thickness of the obscuring layer as 2T.…”
Section: Constraint On Thickness Of Obscuring Layermentioning
confidence: 99%